The era of the unmanned vevicles is coming - Krawczyk Jacek (2021)
The use of Unmanned Vehicles in air, land and water transport is constantly increasing due to their technical and operational capabilities, along with economic advantages. They are used for recreational and commercial purposes by individuals, companies, organisations and state institutions. Particular types of vehicles are at different stages of technical, legislative and implementation advancement. Unmanned vehicles are at different phases of the process of the launch on the market for common use by the public. Railway transport will be the first to undergo widespread and, consequently, full automation, due to the fact that it is already in use and there is a possibility of its safe implementation, which must progress along with the development of technology, science and experience of producers and users.